Seni Mengajar Guru Di Era Digital Dalam Menjangkau Capaian Belajar Siswa Di Yayasan Perguruan Gajah Mada Medan - Rini Armianti Berutu, Dies L Tobing, Satya Nofryanti N, Rosaria Anastasya Sianipar, Anjelina Pasarib (Pusdikra Publishing, 2023)
This article aims to find out how the art of teaching digital teachers can reach student learning outcomes at SMA N 8 Medan. The method used in this research is descriptive qualitative method. Good data. primary and secondary were collected then analyzed and presented descriptively. This journal will discuss how the art of teaching teachers in the digital era, how to overcome the lack of teacher competence, what factors cause low teacher motivation in developing self- quality, and what impact is the lack of teacher competence in the range of student learning outcomes. The findings of the analysis reveal that the art of teaching teachers in the digital era in reaching student learning outcomes at SMA N 8 Medan is by innovating various learning media such as digital media, namely using various learning applications, making learning media interesting, learning methods adapted to the characteristics of students and prioritizing character in learning. Factors that cause low teacher competence in SMA N 8 Medan are the low curiosity of teachers in carrying out learning innovations, not understanding the true meaning of professionalism, and a lack of a sense of responsibility towards themselves as a teacher. The impact arising from the lack of teacher competence is that learning objectives are not achieved for students.